Eurasian Business and Economics Perspectives Proceedings of the 35th Eurasia Business and Economics Society Conference - Bilgin, Mehmet Huseyin; Danis, Hakan; Demir, Ender; Mustafa, Ghulam (Cham : Springer International Publishing : Imprint: Springer, 2022)
EBES conferences have been intellectual hub for academic discussion in economics, finance, and business fields and provide network opportunities for participants to make long lasting academic cooperation. This is the 22nd volume of the Eurasian Studies in Business and Economics (EBES's official proceeding series) which includes selected papers from the 35th EBES Conference - Rome 2021. Due to the COVID-19, the conference presentation mode has been switched to "online/virtual presentation only". In the conference, 142 papers by 302 colleagues from 48 countries were presented. Both theoretical and empirical papers in this volume cover diverse areas of business, economics, and finance from many different regions. Therefore, it provides a great opportunity to colleagues, professionals, and students to catch up with the most recent studies in different fields and empirical findings on many countries and regions.
Part 1. Entrepreneurship -- Chapter 1. Why Immigrant Entrepreneurs are More Prone to Exit Than Non-immigrant Entrepreneurs? -- Chapter 2. Hawkers' Attitude on Environmentally-friendly Food Packaging Practices in Night Market -- Part 2. Human Resources Management & Education -- Chapter 3. Innovation and Creativity Among Individuals in Work Environments: The Effect of Personality, Motivation, Psychological, and Task-oriented Factors -- Chapter 4. Skills Shortages in Post-transition Economies -- Chapter 5. How Hybrid Learning Can Enhance the Student Experience and Teaching Outcomes in the Wake of Covid-19: A Case Study of a Business School in the United Kingdom -- Part 3. Management -- Chapter 6. Knowledge Management in a Political Context: A Case Study About the Members of the German Bundestag -- Chapter 7. The Principlism Method Applied Utilitarianist in Mathematical Calculations for an Ethical Decision -- Part 4. Marketing -- Chapter 8. Neuromarketing: A Review Regarding Marketing Field -- Chapter 9. Innovative Financial Indicators: From Roi to Marketing Roi -- Part 5. Small and Medium-sized Enterprises (SMEs) -- Chapter 10. Analysis of the Relationship Between Strategic Networking and Performance Among Croatian Service Sector SMEs -- Chapter 11. Assessing the Effects and Policy Interventions Amidst Covid-19 Crisis: Focus on Georgian SMEs -- Part 6. Finance -- Chapter 12. The Technological Impact in Finance: A Bibliometric Study of Fintech Research -- Chapter 13. The Factors Determining the Specific Nature of Formation of the Capital Structure: Evidence from Maritime Sector -- Chapter 14. Measuring Corporate Social Responsibility by Constructing an Index: An Empirical Evidence from Oman -- Chapter 15. On the Relationship Between Macroeconomic Factors and S&P BSE Auto Index: An ARDL Approach -- Part 7. Growth & Development -- Chapter 16. Economic Policies and Their Impacts on Growth -- Chapter 17. Three Decades on Renewable Climate Policy: A Bibliometric Analysis -- Chapter 18. The Potential Use of Blockchain Technology for Data Collection and Measurement of Trade in Services -- Part 8. Regional Studies -- Chapter 19. The Design of Fiscal Rules in the European Monetary Union -- Chapter 20. The Perspectives on Non-state Social Protection.
Keywords: Macroeconomics; Management; Industries; Finance; Regional economics; Spatial economics; Macroeconomics and Monetary Economics; Management; Industries; Financial Economics; Regional and Spatial Economics